Manipulations of distractor frequency do not mitigate emotion-induced blindness. Issue 3 (3rd April 2019) - Zhao, Jenna L.; Most, Steven B.
ABSTRACT: Emotional distractors can impair perception of subsequently presented targets, a phenomenon called emotion-induced blindness . Do emotional distractors lose their power to disrupt perception when appearing with increased frequency, perhaps due to desensitisation or enhanced recruitment of proactive control? Non-emotional tasks, such as the Stroop, have revealed that high frequency distractors or conflict lead to reduced interference, and distractor frequency appears to modulate attentional capture by emotional distractors in spatial attention tasks. But emotion-induced blindness is thought to reflect perceptual competition between targets and emotional distractors, and it is unclear whether high frequency emotional stimuli cause less disruption at this relatively early stage of processing. In four experiments, participants searched streams of images for a rotated target image. A negative or neutral distractor appeared before the target, and their relative frequency was manipulated. Across all experiments, the frequency of emotional distractors did not modulate emotion-induced blindness even when participants were explicitly informed that they would appear often or seldom. Thus, increased distractor frequency does not appear to mitigate the priority allotted to emotional distractors during perceptual competition.